Dissemination and Comparison of Genetic Determinants of mcr-Mediated Colistin Resistance in Enterobacteriaceae via Retailed Raw Meat Products - Gelbíčová, Tereza; Baráková, Alžběta; Florianová, Martina; Jamborová, Ivana; Zelendová, Markéta; Pospíšilová, Lucie; Koláčková, Ivana; Karpíšková, Renáta (Frontiers in Microbiology, 2019)
Global food chain may significantly support the dissemination of bacteria resistant to antibiotics around the world. This study was aimed to determine the prevalence and genetic characteristics of Enterobacteriaceae with mcr-mediated colistin resistance from retail meat of different origin. Bacteria of Enterobacteriaceae carrying the mcr-1 gene were detected in 21% (18/86) of the examined samples, especially in turkey meat and liver originating from the EU and non-EU countries (19%) and in rabbit meat imported from China (2%). The examined samples of chicken and other poultry meat and liver, pork and beef were negative for the presence of bacteria carrying mcr-1 to mcr-5 genes. A huge number of isolates belonging to E. coli (n=54), K. pneumoniae (n=6) and Citrobacter braakii (n=1) carrying the mcr-1 gene were obtained. Despite the high heterogeneity of the tested isolates, the mcr-1 gene was localized on only three types of plasmids (IncX4, IncHI2, IncI2). The most frequent type of plasmid was IncX4, which carried the mcr-1 gene in 77% of E. coli and K. pneumoniae isolates from turkey meat and liver samples from the Czech Republic, Germany, Poland and Brazil. Our findings indicated a highly probable interspecies transfer of IncX4 and IncI2 plasmids within one sample meat. The co-resistance of plasmid-mediated colistin resistance encoded by the mcr-1 and ESBL genes was detected in 18% of the isolates. Another noteworthy finding was the fosA3 gene coding for fosfomycin resistance in a multi-drug resistant isolate of E. coli from rabbit meat imported from China. The observed high level of Enterobacteriaceae with plasmids carrying mcr-1 gene from retail meat reflect the need for Europe-wide monitoring of mcr-mediated colistin resistance through the whole food chain.